Colliding Theories and Power Differentials: A Cautionary Tale of Conducting Action Research While Student Teaching - Jennifer M. Conner-Zachocki; Danielle Dias (Networks: An Online Journal for Teacher Research, 2013)
Accounts of student teachers engaging in action research are abundant. Few of those accounts, however, provide insights into the challenges that this context might pose for an action researcher. Using narrative research methods, this study shares the story of one pre-service elementary education teacher who, with the permission of her supervising teacher and student teaching partner, made plans to teach a New Literacies Studies unit during her fourth grade student teaching placement and engage in action research in order to reflect on teaching and learning during that unit. Ultimately, philosophical tensions underpinning the student teacher and supervising’s understandings of literacy and literacy instruction, as well as power differentials that often define the student teacher/supervising teacher relationship, undermined the student teacher’s role as action researcher. Implications for student teachers engaging in action research and their university mentors are discussed.